To multiply the polynomial expression \((x + 2)(x - 4)\), we can use the distributive property (also known as the FOIL method for binomials):
- Multiply the first terms: \(x \cdot x = x^2\)
- Multiply the outer terms: \(x \cdot (-4) = -4x\)
- Multiply the inner terms: \(2 \cdot x = 2x\)
- Multiply the last terms: \(2 \cdot (-4) = -8\)
Now, combine all these results:
\[ x^2 - 4x + 2x - 8 \]
Combine like terms:
\[ x^2 + (-4x + 2x) - 8 = x^2 - 2x - 8 \]
So the final result is:
\[ x^2 - 2x - 8 \]
In the requested format:
___x² + ___x + ___
You would fill it in as:
- 1 (for \(x^2\))
- -2 (for \(-2x\))
- -8 (for the constant term)
So the answer is:
1x² - 2x - 8